Reliability Analysis of a Direct Shear Test of Modified Iron Tailings Based on the Monte Carlo Algorithm - Ping Jiang; Jian Qian; Na Li (Advances in Civil Engineering)
The resource utilization of iron tailings is of great significance for all countries in the world. Considering the particle composition and physicochemical characteristics of iron tailings, fiber and lime were used to modify iron tailings. The fiber content was 0%, 0.25%, 0.5%, 0.75%, and 1%, and the lime content was 0%, 2%, 4%, 8%, and 10%, respectively. Through a direct shear test, the shear stress displacement (τ-δ) curves and shear strength of modified iron tailings, under the action of a 0 freeze-thaw cycle and 1 freeze-thaw cycle, were tested. As statistics have shown that there are uncertainty factors associated with direct shear tests, the shear strength index cohesion c and internal friction angle φ of the modified iron tailings were analyzed using the Monte Carlo method. The results show that the τ-δ curve of the fiber-modified iron tailings is a hardening-type curve and that of the lime-modified iron tailings is a softening-type curve. In the direct shear tests, the main uncertain factors are the specimen diameter, vertical force, and horizontal force. The diameter of the sample obeys a normal distribution, and the vertical and horizontal forces obey a uniform distribution. The results of the Monte Carlo simulation show that both c and φ obey a normal distribution. Under a 95% confidence condition, the effect of fiber on the cohesion on iron tailings is obvious, but the effect on the internal friction angle is not obvious. However, the values of c and φ of the iron tailings are clearly improved by lime. Additionally, the iron tailings modified by a fiber content of 1% and those modified by a lime content of 8% have the best frost resistance.